The Development and Application of Rubrics in Education: A Scopus-Based Systematic Literature Review (2016–2026) - Ahmad Hanafi Nurmawansyah; Aji Joko Budi Pramono (Actual Insight, 2026)
Rubric is an assessment instrument that plays a central role in supporting transparency and consistency of evaluation in education. This study aims to map the development, application, and effectiveness of rubrics in education through the Systematic Literature Review (SLR) approach following PRISMA 2020 guidelines. A literature search was conducted using keywords (